2019
DOI: 10.1099/mgen.0.000313
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis: when the virulence-associated genome backbone imports a prevalence-associated major antigen signature

Abstract: Chlamydia trachomatis is the most prevalent sexually transmitted bacterium worldwide and the causative agent of trachoma. Its strains are classified according to their ompA genotypes, which are strongly linked to differential tissue tropism and disease outcomes [ocular disease, urogenital disease and lymphogranuloma venereum (LGV)]. While the genome-based species phylogenetic tree presents four main clades correlating with tropism/prevalence, namely ocular, LGV, urogenital T1 (more prevalent genotypes) and ur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Further, the detection of recombinant ompA, a known hotspot for recombination in the C. trachomatis genome, in these samples as part of an approximate 12kb exchange could have only been identified by WGS and not by Sanger sequencing alone, highlighting the genetic resolution achieved in this study to understand the evolution of contemporary C. trachomatis strains 40,43,55 . Some studies have reported recombinant forms of both ompA and pmpH, and tracking these and additional known recombinant variants may inform the field on the dynamics of current transmission networks and C. trachomatis tropism in general 9,53,79 . With that said, the high rates of recombination and limited genetic diversity within C. trachomatis strains indicates the need to include a large number of loci dispersed throughout the genome to circumvent false negativity of clinical strain typing, which can now be efficiently achieved by sequencing the whole genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the detection of recombinant ompA, a known hotspot for recombination in the C. trachomatis genome, in these samples as part of an approximate 12kb exchange could have only been identified by WGS and not by Sanger sequencing alone, highlighting the genetic resolution achieved in this study to understand the evolution of contemporary C. trachomatis strains 40,43,55 . Some studies have reported recombinant forms of both ompA and pmpH, and tracking these and additional known recombinant variants may inform the field on the dynamics of current transmission networks and C. trachomatis tropism in general 9,53,79 . With that said, the high rates of recombination and limited genetic diversity within C. trachomatis strains indicates the need to include a large number of loci dispersed throughout the genome to circumvent false negativity of clinical strain typing, which can now be efficiently achieved by sequencing the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…Further, due to low genetic resolution, these methods fail to demonstrate precise inter-and intra-strain recombination events across the genome that contribute to strain diversity [40][41][42][43][44] . Recombination has been important in creating emerging strains of C. trachomatis such as L2b among MSM in many countries of the world and recombinant strains L2/D (termed L2c) and L2b/D-Da in the U.S. and Portugal, respectively 28,[40][41][42][43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to a CT strain in which part of the D/Da ompA gene was integrated by recombination in the L2b ompA gene in an L2 background CT genome. The variant LGV strain caused symptoms and was correctly diagnosed using another LGV typing test that targeted the pmpH gene [30]. We tested DNA from this recombinant ompA LGV strain and were able to detect <50 copies/μL, showing that the pgp3 LGV PCR is also able to detect this recombinant strain.…”
Section: Discussionmentioning
confidence: 96%
“…This strain was named the 'Swedish variant' since it was predominantly found in Sweden [28,29]. Recently Borges et al (2019) reported that some LGV strains were missed by using only ompA typing of CT in Portugal. This was due to a CT strain in which part of the D/Da ompA gene was integrated by recombination in the L2b ompA gene in an L2 background CT genome.…”
Section: Discussionmentioning
confidence: 99%